2019
DOI: 10.1002/ejic.201801488
|View full text |Cite
|
Sign up to set email alerts
|

Borohydride as Magnetic Superexchange Pathway in Late Lanthanide Borohydrides

Abstract: The magnetic characteristics of a series of borohydride‐based systems, including binary α‐/β‐Ln(BH4)3 phases (Ln = Gd, Tb, Dy, Ho, Er, and Tm) with direct Ln–HBH–Ln bridges and selected mixed‐metal systems, LiYb(BH4)4, NaYb(BH4)4, KHo(BH4)4, RbTm(BH4)4, with isolated Ln3+ ions embedded in [Ln(BH4)4]– anions are described for the first time using SQUID magnetometry and DFT+U calculations. Crystal field effects as well as the nature and strength of magnetic superexchange interactions via BH4– ligands are establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…[ 1–3 ] This has been manifested in significant growth of the number of known solvent‐free borohydrides, strongly supported by the development of the synthetic methods, in parallel with the structural identification of the products. [ 4–11 ] Besides the storage of hydrogen and their traditional use in reduction processes, borohydrides are studied in the context of solid‐state ion conduction, [ 12–15 ] magnetic and luminescent properties, [ 16–19 ] or as porous materials, capable for loading of guest molecules. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] This has been manifested in significant growth of the number of known solvent‐free borohydrides, strongly supported by the development of the synthetic methods, in parallel with the structural identification of the products. [ 4–11 ] Besides the storage of hydrogen and their traditional use in reduction processes, borohydrides are studied in the context of solid‐state ion conduction, [ 12–15 ] magnetic and luminescent properties, [ 16–19 ] or as porous materials, capable for loading of guest molecules. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…The observed absorption bands are also similar to those reported for the related derivatives of yttrium borohydride [ 57 ], where the DFT calculations for [(CH 3 ) 4 N][Y(BH 4 ) 4 ] confirmed 12-fold coordination of Y 3+ in the [Y(BH 4 ) 4 ] − complex. [ RE (BH 4 ) 4 ] − complex anion in such geometry is found in numerous RE 3 + borohydrides, also in all the known mixed-cation derivatives of RE (BH 4 ) 3 , RE = Ho, Tm, Yb, namely K[Ho(BH 4 ) 4 ] [ 38 ], Rb[Tm(BH 4 ) 4 ] [ 23 ], [Ph 4 P][Tm(BH 4 ) 4 ] [ 58 ], and M [Yb(BH 4 ) 4 ], M = Li [ 11 ], Na, K [ 39 ], as well as in the related compounds of Sc and Y [ 34 , 57 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although most of studies focus on examining of the process of hydrogen release, several reports indicate at least some degree of reversibility of such systems, which is crucial for their application, e.g., [ 10 ]. Various borohydrides can also serve as precursors of metal borides [ 11 , 12 , 13 , 14 , 15 ] or boron nitride [ 16 ], and some of them have been explored as prospective solid-state electrolytes in Li + batteries [ 17 , 18 , 19 , 20 , 21 ] or luminescent and magnetic materials [ 22 , 23 ], while the borohydride complexes of rare-earth elements were also tested for organic catalysis [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 This proposal is consistent with a recent study of magnetic exchange in [Ln(BH 4 ) 3 ] (Ln = Gd–Tm), in which it was found that {HBH} bridges between the metal centres allow antiferro- or ferro-magnetic exchange, albeit with very small coupling constants. 43 …”
Section: Resultsmentioning
confidence: 99%